Nurses’ attitudes toward web-based learning and their impact on clinical performance, job satisfaction, and turnover: a cross-sectional study in Saudi Arabia - Mohammed Abu Thiyab; Ahmed Nahari (BMC Nursing)
Abstract Background Nurses face challenges in accessing professional development because of high workloads, workforce shortages, and shift-based schedules. Limited availability of and negative perceptions toward web-based learning may affect clinical performance and job satisfaction, potentially increasing turnover rates. This study aimed to examine the impact of nurses’ attitudes toward web-based learning on clinical performance, job satisfaction, and anticipated turnover in Saudi Arabia. Methods A nonexperimental, cross-sectional quantitative design was used. The study was conducted in various healthcare settings in Saudi Arabia using a nonprobability convenience sampling method. Data were collected using the Attitudes Toward Web-Based Continuing Learning Survey to assess attitudes toward online learning, the Individual Work Performance Questionnaire to evaluate clinical performance, the Nursing Workplace Satisfaction Questionnaire to measure job satisfaction, and the Anticipated Turnover Scale to assess turnover intention. Results A total of 177 registered nurses participated in the online survey. Data were analyzed using descriptive statistics, inferential statistics, and linear regression analysis. The findings revealed a significant, moderate positive correlation between attitudes toward web-based learning and clinical performance (r = 0.314, p < 0.001), indicating that more favorable attitudes were associated with higher clinical performance. A significant, weak negative correlation was observed with job satisfaction scores (r = − 0.224, p = 0.004), indicating that more favorable attitudes were associated with greater job satisfaction. No significant association was found between attitudes toward web-based learning and anticipated turnover (r = − 0.083, p = 0.300). Regression analysis showed that attitudes toward web-based learning significantly predicted clinical performance (β = 0.331, p < 0.001) but did not significantly predict job satisfaction (β = − 0.148, p = 0.061) or turnover intention (β = − 0.035, p = 0.658). Conclusions The study highlights web-based learning as an effective and flexible training modality for nurses, offering accessible professional development that enhances knowledge and clinical competency. Nurses demonstrated positive attitudes toward web-based learning, supporting its potential to improve clinical performance and job satisfaction. Future initiatives should focus on optimizing and expanding web-based learning programs to maximize their impact on nursing education and workforce development.